PENGARUH TAYANGAN IKLAN FATIGON HYDRO+ DI TELEVISI TERHADAP PEMBENTUKKAN BRAND AWARENESS - Purba, Zulham Rizky (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
The number of companies that manufacture and market products isotonic beverage, making competition between companies has become very tight. Of each company is trying to introduce a product. One is the product being advertised Fatigon Hydro + through the medium of television with a fairly high frequency of exposure on several TV stations. The aim is that the higher the brand awareness of the product Fatigon Hydro + in the community.